Dynamic social behavior algorithm for real-parameter optimization problems and optimization of hyper beamforming of linear antenna arrays - PrajindraSankar K.; Kiong T.S.; SiawPaw J.K. (Elsevier Ltd, 2023)
Animals; Antenna arrays; Antennas; Beam forming networks; Beamforming; Behavioral research; Bioinformatics; Evolutionary algorithms; Global optimization; Problem solving; Swarm intelligence; Bio-inspired algorithms; Co-operative behaviors; Global optimization problems; Meta heuristics; Optimization algorithms; Optimization techniques; Real-parameter optimization; Swarm algorithms; Optimization